Adsorption of Carbon Dioxide on Porous Catalyst Materials at Near-Critical Conditions - Fabio Capezzuoli; Frantisek Stepanek; David Chadwick (Adsorption Science & Technology)
Herein, the construction of a manometric adsorption apparatus has been described and an experimental method has been developed to measure the adsorption of carbon dioxide on porous materials at sub-critical pressures. The materials used are silica gel and silica loaded with 5 mol% ZnO; γ-alumina and alumina with 5 mol% ZnO. It was observed that the addition of zinc oxide causes a 50–100% increase of the adsorbed amount at 350 K. However, this manometric apparatus is only suitable for relatively large adsorbed amounts due to its sensitivity and precision limitations.